Pengujian Metode Kuantitasi Untuk Melakukan Kompresi Citra RGB - Pilipus Tarigan; Zekson Arizona Matondang (Yayasan Kita Menulis, 2019)
At present the use of RGB images is a necessity in various fields. However, its use is constrained by a large file capacity, but it is possible to compress the image that is owned as needed. With the quantization method, the R matrix, the G matrix and the B matrix will be reduced, so that the number of bits used to represent the image will be reduced. Because the number of bits is reduced, the file size becomes smaller. The quantization method is included in the Lossy Compression category, so the compressed image cannot be decompressed again because there is information missing.